2002
DOI: 10.2214/ajr.179.2.1790409
|View full text |Cite
|
Sign up to set email alerts
|

Using Contrast-Enhanced MR Cholangiography with IV Mangafodipir Trisodium (Teslascan) to Evaluate Bile Duct Leaks After Cholecystectomy: A Prospective Study of 11 Patients

Abstract: Contrast-enhanced MR cholangiography with IV mangafodipir trisodium can successfully detect the presence and location of bile duct leaks in patients suspected of having such leaks after undergoing cholecystectomy. More research is necessary before acceptance of this examination as routine in the workup of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Recent studies have shown the utility of contrastenhanced MRC especially in visualizing non-dilatated bile ducts (e.g., in living liver donors) and biliary leaks [4,5,11]. Currently, three different hepatobiliary contrast agents are available for contrast-enhanced MRC: mangafodipir trisodium (Mn-DPDP; Teslascan; GE Healthcare, Oslo, Norway), gadobenate dimeglumine (Gd-BOPTA; MultiHance, Bracco Imaging, Milan, Italy), and gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA, gadoxetic acid; Primovist, Bayer Schering Pharma, Berlin, Germany).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the utility of contrastenhanced MRC especially in visualizing non-dilatated bile ducts (e.g., in living liver donors) and biliary leaks [4,5,11]. Currently, three different hepatobiliary contrast agents are available for contrast-enhanced MRC: mangafodipir trisodium (Mn-DPDP; Teslascan; GE Healthcare, Oslo, Norway), gadobenate dimeglumine (Gd-BOPTA; MultiHance, Bracco Imaging, Milan, Italy), and gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA, gadoxetic acid; Primovist, Bayer Schering Pharma, Berlin, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that contrast-enhanced MRC is particularly useful for the evaluation of biliary tract abnormalities in healthy individuals (e.g., potential living liver donors), and in patients suspected to have a biliary leak [1,[3][4][5]. Although contrast-enhanced MRC is increasingly used by radiologists, there is paucity of data in the literature with regard to the degree and extent of biliary excretion of hepatobiliary contrast agents.…”
Section: Introductionmentioning
confidence: 99%
“…Vitellas et al [18] performed MR cholangiography with intravenous mangafodipir trisodium (Teslascan) in patients with a possible bile leak after cholecystectomy. Teslascan is a T1-weighted contrast agent that is excreted primarily through the biliary tract.…”
Section: Postoperative Detectionmentioning
confidence: 99%
“…When suspected diagnosis can be made by endoscopic retrograde cholangiopancreatography (ERCP) which is gold standard examination for confirming the diagnosis. The disadvantages of this approach include invasiveness and a high rate of false-negatives [7]. In centers where MR cholangiography is the initial investigation of choice for biliary pathologies the detection rate is very high.…”
Section: Discussionmentioning
confidence: 99%